Gag Reflex: No More A Gag To A Dentist The Behavioral Techniques, Pharmacological Techniques, Acupressure and Acupuncture in Controlling the Gag Reflex - A Review (Bangladesh Journal of Medical Science, 2012)
Gagging in dental patients can be disruptive to dental treatment and may be a barrier to a patient care, preventing the provision of treatment and the wearing of prostheses. Many management techniques have been described to control the gagging. This article reviews the literature on various management strategies described to prevent and control the gagging. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9816 BJMS 2012; 11(1): 12-17